Le cuisinier françois [and three other 17th century French cookery books], presented by Jean-Louis Flandrin and Philip and Mary Hyman - Davidson, Alan E (Petits Propos Culinaires, 2024)
Le cuisinier françois [and three other 17th century French cookery books], presented by Jean-Louis Flandrin and Philip and Mary Hyman: Bibliothèque Bleue, Montalba, Paris, 1983. 543 pp. (of which 100 are introductory matter), 90 francs (or £9.00 from Prospect Books).